Validation of proteomic biomarkers previously found to be differentially expressed in women with Polycystic Ovary Syndrome: a cross-sectional study. (March 2014) - Haoula, Zeina; Shaw, Barry; Daykin, Clare; Hodgman, Charlie; Layfield, Robert; Atiomo, William
Abstract Objectives: The aim of this study was to independently validate proteomic biomarkers previously reported to be differentially expressed in women with Polycystic Ovary Syndrome (PCOS) compared with controls. This study focused on plasma proteomic biomarkers. Methods: This was a cross-sectional study at the University of Nottingham, in which samples from 30 PCOS and 30 control women were analysed by Western blotting. Results: Mean abundance ratios from Western blots of plasma total haptoglobin and haptoglobin beta proteins were 1.25 (CI 1.11–1.4) and 1.24 (CI 1.04–1.44). The mean abundance ratio from the blots of alpha-2 macroglobulin was however 1.05 (CI, 1–1.1). The mean PCOS/control BMI ratio was 1.18 (CI 1.17–1.20). There was no correlation between PCOS/control BMI ratio and alpha-2 macroglobulin, total haptoglobin and haptoglobin beta abundance ratios. There was also no correlation between PCOS/control insulin ratio and alpha-2 macroglobulin, total haptoglobin and haptoglobin beta abundance ratios. Conclusions: Total haptoglobin and haptoglobin beta chain protein abundance was found to be elevated in women with PCOS compared with controls. We were unable to confirm decreased alpha-2 macroglobulin levels as reported in a previous study. Independent validation studies are required to validate early promising proteomic biomarkers in PCOS.